Problems and needs In helping older people with dementia with daily activities: Perspectives of Thai caregivers - Jiranan Griffiths (2018)
© The Author(s) 2015. Introduction: Caring for people with dementia can be stressful and demanding. The purpose of this qualitative descriptive study was to investigate the problems and needs of caregivers who help older people with dementia to do activities of daily living. Method: Thirty caregivers who took older people with dementia to get treatment at a memory clinic in a hospital in the north of Thailand were interviewed using a semistructured interview. Transcribed data were analysed using inductive analysis. Findings: The analysis generated five themes related to problems experienced by caregivers: toileting is the hardest job, lifting causes back pain, loss of memory problems, economic hardships and psychological distress. These issues aggregated into support needs from three sources: information and rehabilitation services from health professionals, assistance with everyday tasks from family members and financial support from society. Conclusion: The findings reveal that the kind of support Thai caregivers seek from various groups differs according to their perceived expertise and availability. Further studies are needed to explore how that assistance might be delivered and whether it is in fact helpful.